Low-temperature regeneration of novel polymeric adsorbent on decamethylcyclopentasiloxane (D5) removal for cost-effective purification of biogases from siloxane - Jung, Hyounduk; Lee, Dae-Young; Jurng, Jongsoo (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
Biogas, a fuel used to generate electricity, contains siloxanes that can damage combustion engines, leading to, expensive repairs and service interruptions. Activated charcoal is used to reduce the silicon content. Since siloxanes are difficult to desorb from the material, the adsorbent beds have to be replaced regularly. Thermal swing adsorption (regeneration at 250 degrees C) using silica gel is an effective method to remove siloxane from biogas. Also, it would be advantageous and cost-effective if the adsorption material could be regenerated easily at a lower temperature. In the present study, a novel polyacrylic acid (PAA)-based polymer adsorbent was studied as a biogas siloxane adsorbent exposed to adsorption/regeneration cycles. At room temperature (25 degrees C), the D5 adsorption capacity of RPA was 21.55 mg/g adsorbent, which is similar to 70% of the adsorption capacity of silica gel. The thermal desorption of siloxane (D5) from the exhausted polymer was more than 95%, which afforded a similar capacity for siloxane (D5) adsorption, at a low regeneration temperature of 80 degrees C, where no siloxane regeneration was observed using conventional silica gel. (C) 2017 Elsevier Ltd. All rights reserved.